2021
DOI: 10.1016/j.sjbs.2021.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity and mutational analysis of New Delhi Metallo-β-lactamase (NDM) producing E. coli strains from pediatric patients in Pakistan

Abstract: The evolution of NDM genes ( bla NDM ) in E. coli is accounted for expansive multidrug resistance (MDR), causing severe infections and morbidities in the pediatric population. This study aimed to analyze the phylogeny and mutations in NDM variants of E. coli recovered from the pediatric population. Carbapenem-resistant clinical strains of E. coli were identified using microbiological phenotypic techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…whereas the result of bacteria Pseudomonas aeruginosa for this gene was 4( 33.3%) The results of our study are similar to those from previous studies in Diyala, Iraq [45][46][47] in Iran, It is similar to the result of this study because it contains this gene NDM (25%) ; (4%) ; (35%) respectively. The result of this gene among bacteria Escherichia coli was 1(10%),this result agreed with the results in Pakistan [48][49][50] who observed in these studies that its isolates carry this gene NDM (3.5%) ; (12.9% ) ; (13.5% ) respectively. While it does not agree with this study in Wasit [17] because its results do not contain this gene NDM.…”
Section: Ndmsupporting
confidence: 90%
“…whereas the result of bacteria Pseudomonas aeruginosa for this gene was 4( 33.3%) The results of our study are similar to those from previous studies in Diyala, Iraq [45][46][47] in Iran, It is similar to the result of this study because it contains this gene NDM (25%) ; (4%) ; (35%) respectively. The result of this gene among bacteria Escherichia coli was 1(10%),this result agreed with the results in Pakistan [48][49][50] who observed in these studies that its isolates carry this gene NDM (3.5%) ; (12.9% ) ; (13.5% ) respectively. While it does not agree with this study in Wasit [17] because its results do not contain this gene NDM.…”
Section: Ndmsupporting
confidence: 90%
“…Molecular analysis of NDM-1gene in clinical isolates of Enterobacteriaceae form two tertiary hospital in Sakaka, Saudi Arabia found that bla NDM-1 and bla NDM harbored isolates were respectively accounted for 63.2 and 36.8% (Ejaz et al, 2020). In asian padiatric patients, carbapenem resistance were accounted for 24% of total E. coli and the NDM producing E. coli strains harbored more NDM-5 (50%) than NDM-1 (46%) and NDM-4 (3.5%)variants (Nosheen et al, 2020;Nosheen et al, 2021). Until now, multiple NMD-1 inhibitors have been designed and tested, but there is still no inhibitor on market.…”
Section: Discussionmentioning
confidence: 99%
“…In K. pneumoniae studies reported variable carbapenem resistance levels i.e., 37.5% (75/200) [ 113 ], 32.5% (39/120) [ 114 ], the isolates were clinical and human-animal-environment origin, respectively. Similarly in E. coli variable levels of resistance was observed 3.7% (12/324) from blood and cerebrospinal cultures [ 115 ], 7.4% (113/1522) from paediatric patients [ 116 ], 28.3% (184/650) from diagnostic samples [ 117 ], and 49.5% (98/198) from tertiary care outpatients [ 118 ]. These studies reported bla NDM to be the most prevalent genetic determinant for carbapenem resistance.…”
Section: Resultsmentioning
confidence: 99%